1979
DOI: 10.1107/s0567740879006312
|View full text |Cite
|
Sign up to set email alerts
|

Electron-density distribution in crystals of KCuF3 with Jahn–Teller distortion

Abstract: The electron-density distribution in crystals of K+[CuFa] -has been investigated on the basis of X-ray intensity data collected by diffractometry at room temperature. The crystal has a distorted perovskite structure, containing Cu 2+ ions at pseudo-tetragonally deformed octahedral sites. On the deformation-density map, positive peaks were observed on the longest Cu-F bonds and negative peaks on the shortest Cu-F near the Cu 2+ ion. When aspherical scattering factors were used for Cu 2+ by assuming the hole of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…The density near the Cu nucleus has a remarkable resemblance to the corresponding region of the difference map for KCuF3 shown in their Fig. 2(b) by Tanaka et al (1979). Closely similar features are observed for other Cu 2÷ complexes, which will be described in later papers in this series.…”
Section: Difference Densitiessupporting
confidence: 61%
See 1 more Smart Citation
“…The density near the Cu nucleus has a remarkable resemblance to the corresponding region of the difference map for KCuF3 shown in their Fig. 2(b) by Tanaka et al (1979). Closely similar features are observed for other Cu 2÷ complexes, which will be described in later papers in this series.…”
Section: Difference Densitiessupporting
confidence: 61%
“…In a study of the electron density in KCuF3, Tanaka, Konishi & Marumo (1979) observed a distorted distribution. Some of the distortion can be related to differences in the lengths of the Cu-F vectors.…”
Section: Jahn-teller Distortionsmentioning
confidence: 99%
“…As to reflexions with very strong ELECTRON-DENSITY DISTRIBUTIONS IN KMnF a AND KNiF 3 and 0.054 and 0.070 for KNiF 3, respectively. Using the method of Becker & Coppens (1974a,b, 1975 (Tanaka, Konishi & Marumo, 1979) and KCoF 3 crystals (Kijima, Tanaka & Marumo, 1981). In order to avoid interaction of extinction parameters with scale factors and temperature factors, we introduced double scale factors, one for reflexions with sin 8/;~ <_ 0.6 A -~ and the other for reflexions with sin 0/2 > 0.6/k -~.…”
Section: Methodsmentioning
confidence: 99%
“…0.11 (7) 754 (2) 751 (3) 750 (2) 1989 (5) 1998 (7) 1992 (5) 777 (12) 795 (17) 779 (12) 3518 (21) 3472 (29) 3523 (21) 889 (15) 916 (22) 902 (15) 2336 (75) 2761 (115) 2372 (76) 937 (16) 958 (23) 951 (16) 161 (33) 216 (50) field were given by Tanaka, Konishi & Marumo (1979, 1980. The scattering factors of the Ar core and the orbital scattering factors of the 3d electrons, (J0)aa, (J2)3a and (J4 >3d were taken from International Tables for X-ray Crystallography (1974).…”
Section: Type Of Refinementmentioning
confidence: 99%
See 1 more Smart Citation